Off-Label Medicine Use In Neonatal Intensive Care Unit Of A Secondary Hospital Of Ad Dakhiliyah Governorate Of Oman - Mohammed Al Hajri, Najiya Amur; Haridass, Sujith; Thomas, Sabin (Journal of Neonatal Surgery, 2025)
Off-label drug use, defined as the prescription of medications for indications, dosages, or routes not sanctioned by regulatory authorities, is prevalent in neonatal intensive care units (NICUs). This prevalence is primarily attributed to the limited availability of evidence-based, regulatory-approved options for neonates. However, such practices raise concerns regarding safety and standardization. In Oman, there is a paucity of data on off-label prescribing within neonatal populations. This study aimed to evaluate the prevalence, patterns, and clinical associations of off-label medication use among neonates admitted to the NICU at Nizwa Hospital. A retrospective cross-sectional analysis was conducted over an 18-month period (January 2023–June 2024), involving neonates aged ≤28 days who received at least one off-label medication. Data were sourced from the hospital’s Al Shifa Plus system and the Vigiflow pharmacovigilance platform. Of the 638 NICU admissions, 182 neonates (28.5%) received off-label prescriptions. The primary reasons for off-label use were unapproved routes of administration (47.2%) and age-specific contraindications (22.4%). Frequently used off-label medications included sodium chloride 3% and omeprazole, with 25.9% classified as high-alert drugs. Significant associations were identified between the number of off-label drugs and discharge outcomes (p = 0.019), as well as between gender and discharge disposition (p = 0.012). No adverse drug reactions were reported. These findings underscore the necessity for neonatal-specific prescribing guidelines, pharmacist-led medication reviews, and enhanced pharmacovigilance and training initiatives to promote safer and more consistent medication use in NICUs.